PEMBELAJARAN BERBASIS LABORATORIUM PAI DI SMK MODERN AL-RIFA’IE - Laili Noor Rochmah; Moh Eko Nasrulloh (Jurnal Tinta: Jurnal Ilmu Keguruan dan Pendidikan, 2021)
Islamic Education (PAI) is given by following the guidance that religion is taught to people with a vision that is to produce a man who is godfearing to Allah SWT and noble, and aims to realize an honest, just, ethical, respectful, disciplined, harmonious and productive human being, both individual and social. The demands of this vision encourage the establishment of PAI laboratories in accordance with the level of education. This research aims to evaluate the condition or benefits of PAI laboratories in schools judging by the standard level, utilization, assessment of students and determining factors of PAI laboratory management. The method in this study is qualitative evaluative, with case studies at SMK Modern Al-Rifa'ie Malang. The results showed that the laboratory of SMK Modern Al-Rifa'ie has not reached the standard level, because of the new formation of pai laboratory but the management of PAI laboratory has been at an adequate utilization stage. It can be understood by the positive assessment given by students and support for the laboratory management factor pai SMK Modern Al-Rifa'ie.